Validating diverse human body models against side impact tests with post-mortem human subjects - Hwang, Eunjoo; Hu, Jingwen; Reed, Matthew P. (Journal of biomechanics, 2020)
This study aimed at evaluating the ability of morphed finite element (FE) human body models (HBMs) to reproduce the impact responses of post-mortem human subjects (PMHS) with various stature and shape. Ten side impact tests previously performed using seven PMHS under 3 m/s and 8 m/s impact velocities were selected for model evaluation. With weight, stature, sex, and age of PMHS, seven FE HBMs were developed by morphing the midsize male THUMS model into the target geometries predicted by the statistical skeleton and external body shape models. The model-predicted force histories, accelerations along the spine, and deflections in the chest and abdomen were compared to the test data. For comparison, simulations in all testing conditions were also conducted with the original midsize male THUMS, and the results from the THUMS simulations were scaled to the weight and stature from each PMHS. The CORrelation and Analysis (CORA) was used to evaluate the model accuracy, with CORA scores close to one indicating excellent agreement. Ten simulations using the morphed models exhibited 0.80 ± 0.01, 0.80 ± 0.01, 0.78 ± 0.02, and 0.78 ± 0.02 CORA scores for the impact forces to the thorax, abdomen, iliac-wings, and greater-trochanter, respectively; the corresponding CORA scores with the original THUMS were markedly lower at 0.60 ± 0.06, 0.69 ± 0.05, 0.71 ± 0.05, and 0.69 ± 0.04; while those for the scaled THUMS were 0.65 ± 0.05, 0.71 ± 0.05, 0.73 ± 0.05, and 0.72 ± 0.02, also lower than the morphed models. Across all simulations, the morphed HBMs demonstrated significantly higher accuracy than the THUMS with or without scaling. These results suggested the necessity of accounting for size and shape effects on predicting human responses in side impacts.